Co-Design of Wideband Polarization-Agile Phased-Array Antennas and Low-Noise Amplifiers for the Next Generation Radio Telescopes - Baelemans, Rene Adrianus Cornelis (Curtin University, 2022)
The next generation of radio-astronomy telescopes in the UHF or decimetre band require phased-array technologies which can provide a high sensitivity, large bandwidth, high polarization purity, and a large Field-of-View. To this end, this thesis will present and discuss the capacitively-connected dipole array including a novel small-scale intermediate experimental validation method and a comprehensive description of its performance as a radio-astronomy instrument.